OPTIMALISASI PAJAK JASA PENDIDIKAN: DALAM UPAYA PEMERATAAN PENDIDIKAN - Siregar, Nancy Mayriski; Munthe, Desi Triana (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2023)
Tax Planning Tax Planning is an effort to save taxes This study seeks to examine the impact of changes in the taxation scheme on VAT for Education Services. Education services, which were originally excluded from the object of VAT, caused considerable tax expenditure, but their implementation has not been on target. The HPP Law changes the taxable service exemption scheme to provide VAT facilities in the form of exemption or non-collection. The research method used is descriptive qualitative. To ensure that the provision of these facilities is on target, the government needs to establish a certain classification for the provision of educational services with a regulation whose preparation is coordinated with the relevant technical ministries. This research is expected to be a reference for stakeholders in policy formulation for the realization of the principles of justice and equity in education as well as optimization of state revenue.